Ordering and polytypism in A₃ᴵᴵB₂ⱽ crystals - Chuiko, G.P.; Don, N.L.; Ivchenko, V.V. (Functional Materials, 2005)
The ordering processes of stoichiometric vacancies within cationic sublattices were considered for Zn₃Р₂, Cd₃Р₂, Zn₃As₂, Cd3As₂. It has been shown that two different types of ordering are possible in these crystals: positional and orientational. Typical energies for the first of them have been estimated to be 78, 71, 66 and 62 meV, respectively. It has been found that the mutual transformations of tetragonal phases could be interpreted as standard transitions between different polytypes.